2017
DOI: 10.1038/s41598-017-10730-2
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomics analysis of salt stress tolerance in the roots of the mangrove Avicennia officinalis

Abstract: Salinity affects growth and development of plants, but mangroves exhibit exceptional salt tolerance. With direct exposure to salinity, mangrove roots possess specific adaptations to tolerate salt stress. Therefore, studying the early effects of salt on mangrove roots can help us better understand the tolerance mechanisms. Using two-month-old greenhouse-grown seedlings of the mangrove tree Avicennia officinalis subjected to NaCl treatment, we profiled gene expression changes in the roots by RNA-sequencing. Of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(61 citation statements)
references
References 109 publications
2
56
0
Order By: Relevance
“…Mangroves have aerial, photosynthesizing roots, which contribute to carbon gain and enable root respiration in anaerobic soils, using both atmospheric and photosynthetically regenerated oxygen (Kitaya et al, 2002). Therefore, although various photosynthesis genes frequently express only in basal levels in roots of the model plant, Arabidopsis thaliana (Klepikova, Kasianov, Gerasimov, Logacheva, & Penin, 2016), they may express in higher levels in mangroves, even during the seedling stage, when aerial roots are generally absent, as observed in A. germinans , and in the congeneric A. officinalis (Krishnamurthy et al, 2017). Differential transcripts expression analyses revealed that photosynthesis-associated transcripts were enriched, mainly in roots and stems from the DET-Arid set.…”
Section: Resultsmentioning
confidence: 99%
“…Mangroves have aerial, photosynthesizing roots, which contribute to carbon gain and enable root respiration in anaerobic soils, using both atmospheric and photosynthetically regenerated oxygen (Kitaya et al, 2002). Therefore, although various photosynthesis genes frequently express only in basal levels in roots of the model plant, Arabidopsis thaliana (Klepikova, Kasianov, Gerasimov, Logacheva, & Penin, 2016), they may express in higher levels in mangroves, even during the seedling stage, when aerial roots are generally absent, as observed in A. germinans , and in the congeneric A. officinalis (Krishnamurthy et al, 2017). Differential transcripts expression analyses revealed that photosynthesis-associated transcripts were enriched, mainly in roots and stems from the DET-Arid set.…”
Section: Resultsmentioning
confidence: 99%
“…Microarrays, serial analysis of gene expression and RNA sequencing (RNA-Seq) are the three most commonly used methods for transcriptome analysis in gene expression studies [28, 29]. RNA-Seq, which allows for the near-complete characterization of transcriptomic events occurring in a specific tissue at a certain time, has been widely applied and proven particularly useful in non-model plants, including sugarcane [28, 3032]. For transgenic plants, a number of studies to date have used transcriptome analysis to study gene expression or assess the impact of genetic engineering [29, 33–36].…”
Section: Introductionmentioning
confidence: 99%
“…Rapid adjustment to new conditions may explain the high salinity tolerance of halophytes, such as mangroves, and this may be an important mechanism for improved salt tolerance (Krishnamurthy et al 2017;Liang et al 2012;Zhu 2001). Secondly, the rapid onset of the initial osmotic adjustments to counteract the immediate reduction in plant growth due to salinity stress, requires instant rootto-shoot signalling once salt has been detected at the roots (Batistič and Kudla 2010;Gilroy et al 2014;Roy et al 2014;Roy et al 2011;Shabala et al 2016).…”
Section: Transgenics Adapt To New Conditions Faster Than the Wild Typementioning
confidence: 99%